A Device for Continuous Monitoring of True Central Fixation Based on Foveal Birefringence - Gramatikov, Boris; Irsch, Kristina; Müllenbroich, Marie; Frindt, Nicole; Qu, Yinhong; Gutmark, Ron; Wu, Yi-Kai; Guyton, David (Annals of biomedical engineering, 2013)
A device for continuous monitoring of central fixation utilizes birefringence, the property of the Henle fibers surrounding the human fovea, to change the polarization state of light. A circular scan of retinal birefringence, where the scanning circle encompasses the fovea, allows identification of true central fixation—an assessment much needed in various applications in ophthalmology, psychology, and psychiatry. The device allows continuous monitoring for central fixation over an extended period of time in the presence of fixation targets and distracting stimuli, which may be helpful in detecting attention deficit hyperactivity disorder, autism spectrum disorders, and other disorders characterized by changes in the subject’s ability to maintain fixation. A proof-of-concept has been obtained in a small study of ADHD patients and normal control subjects.